Prevalence and phylogenetic analysis of Mycobacterium avium subsp. paratuberculosis in cattle in Mosul city, Iraq - Sadam D. Hasan; Mohammad A. Altaliby; Amer H. Taha; Karam M. Abdulrazzaq (Iraqi Journal of Veterinary Sciences)
Mycobacterium avium subsp. paratuberculosis (MAP) is a globally distributed infection that causes chronic enteritis, fluctuating milk production, emaciation, and various degrees of diarrhea. It is also a public health concern. This task investigates the molecular prevalence of MAP in cows along with a phylogenetic analysis of this microorganism in Mosul City, Iraq. 176 fecal specimens were taken from healthy, diarrheic and emaciated cows of different ages and origins. The detection of gene IS900 of MAP revealed that 5.6% (10/176) of tested cows were confirmed using molecular technique. No significant prevalence between the cow’s origin and a significantly higher prevalence of the MAP was recorded on cows over 5 years old and with symptoms. Furthermore, in this study, two sequences of Mycobacterium avium subsp. paratuberculosis were deposited in GenBank (PP976335.1 and PP976335.1); phylogenetically the study strains showed 100% identity near MAP strain in Saudi Arabia under the accession number (MN928512.1) and 99.85% identity with Spain, Germany and South Korea strain accession numbers (FJ775181.1, CP053068.1 and CP033909.1) respectively. Overall, this result showed that the IS900 gene may be used as a molecular tool to identify MAP in cows. In order to monitor, treat, and manage paratuberculosis in cows in Mosul, Iraq, further epidemiological research and isolation are needed.